Dialog Galon - Februarto, Dito; Apriani, Arni; Setiaji, Deden (CV. ITTC INDONESIA, 2025)
This article explores the use of water gallon containers as an alternative instrument in contemporary music composition. Inspired by daily experiences, the work 'Dialog Galon' investigates the unique sonic potential of plastic gallons through various playing techniques. The methods used include experimental sound exploration, qualitative observation, and performance practice. The result shows that plastic gallons produce distinctive acoustic textures, offering rich sonic diversity and ecological value in music creation. This work contributes to the expansion of musical vocabulary and supports sustainable creative practices.